2007
DOI: 10.1158/1535-7163.mct-07-0067
|View full text |Cite
|
Sign up to set email alerts
|

A novel treatment strategy targeting Aurora kinases in acute myelogenous leukemia

Abstract: The Aurora kinases play an important role in chromosome alignment, segregation, and cytokinesis during mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
101
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 21 publications
(29 reference statements)
7
101
1
1
Order By: Relevance
“…These results are in agreement with the recent study of Ikezoe et al 43 who showed aberrant expression of Aurora Cells were harvested 48 hr after transfection. Luciferase activity was analyzed as described in ''Material and methods'' section.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with the recent study of Ikezoe et al 43 who showed aberrant expression of Aurora Cells were harvested 48 hr after transfection. Luciferase activity was analyzed as described in ''Material and methods'' section.…”
Section: Discussionsupporting
confidence: 93%
“…Determination of mitotic activities of cardiomyocytes under different treatments was done as described previously [13], with some modifications. Briefly, the cells were trypsinized, washed with PBS, and fixed in 75% ethanol at 4 °C for at least 18 h. Immunofluorescence staining with an Alexa Fluor 488 conjugated antibody to phosphorylated Histone-3 (Ser10, 1:10, Cell Signaling Technology, Inc., Danvers, MA), which is a mitosis-specific marker, was performed on the fixed cardiomyocytes.…”
Section: Assessment Of Mitosismentioning
confidence: 99%
“…14 We have shown recently that hematological malignant cells including those from acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), as well as chronic myeloid leukemia aberrantly expressed Aurora A and B kinases. 15 In addition, we have shown that ZM447439, a novel and selective inhibitor of Aurora A and B kinases, effectively induced growth arrest and apoptosis of a variety of types of leukemia cells. 15 Studies conducted by other groups noted that the phenotype of HeLa cells after their exposure to ZM447439 was similar to that induced by knock down of the Aurora B kinase gene.…”
mentioning
confidence: 94%
“…15 In addition, we have shown that ZM447439, a novel and selective inhibitor of Aurora A and B kinases, effectively induced growth arrest and apoptosis of a variety of types of leukemia cells. 15 Studies conducted by other groups noted that the phenotype of HeLa cells after their exposure to ZM447439 was similar to that induced by knock down of the Aurora B kinase gene. 16 We, therefore, hypothesized that Aurora B might be a more favorable molecular target for cancer therapy than Aurora A.…”
mentioning
confidence: 94%